Patient‐centred care in haemophilia: Patient perspectives on visualization and participation in decision‐making. Issue 6 (17th September 2019) - van Balen, Erna C.; Krawczyk, Marian; Gue, Deborah; Jackson, Shannon; Gouw, Samantha C.; van der Bom, Johanna G.; Sawatzky, Richard
Abstract: Introduction and Aim: The British Columbia Adult Haemophilia Team recently adopted a patient‐centred care approach. The team presented visual information on an individual's pharmacokinetic profile and bleed history and encouraged patients to participate in treatment decisions. This qualitative study explored how this approach changed patients' understanding of haemophilia and how it facilitated them to make treatment decisions. Methods: We interviewed 18 males with mild, moderate or severe haemophilia, using a convenience sample from the adult haemophilia clinic at St. Paul's hospital in Vancouver, Canada. Interviews were recorded and transcribed verbatim and analyzed using descriptive content analysis. Results: Most participants reported that reviewing visual information with the Clinic Team helped them in their communication with their care providers during their annual review clinic appointment. Despite this improved communication, for some the most important feature of their treatment was that they had switched from on‐demand treatment to prophylactic treatment in recent years and were able to prevent bleeds. Almost half of the participants reported that the visual information presented increased their understanding of haemophilia and the pharmacokinetics of coagulation factor. Three patients improved their treatment adherence or had changed their prophylaxis schedules based on this. Most participants felt that they were involved in decision‐making about their treatment schedule, which they appreciated. On the other hand, two participants thought the Clinic Team should make these decisions. Conclusion: Participants perceived the patient‐centred prophylaxis approach helpful because it enhanced communication with the Clinic Team, increased their understanding of haemophilia and pharmacokinetics of coagulation factor and facilitated treatment decisions.